Concomitant cannabis abuse/dependence in patients treated with opioids for non‐cancer pain. (5th August 2015) - Hefner, Kathryn; Sofuoglu, Mehmet; Rosenheck, Robert
<x xml:space="preserve">Abstract</x> Background and Objectives Cannabis use is common among patients taking prescription opioids, although rates of concomitant cannabis use disorder (CUD) have been largely unexamined. CUD may increase safety risks in those taking opioid pain medications but it is unknown whether cannabis and opioids function as substitutes (cannabis use is associated with less prescription opioid use), or rather as complements (cannabis is associated with increased use of prescription opioids). Methods We examined rates of CUD in a national sample of Veterans Health Administration (VHA) patients (n = 1, 316, 464) with non‐cancer pain diagnoses receiving opioid medications in fiscal year 2012. Using bivariate analysis to identify potentially confounding variables associated with CUD (eg, psychotropic medication, other substance use disorders) in this population, we then utilized logistic regression to examine rates of cannabis use disorder among individuals receiving different numbers of opioid prescriptions (0, 1–2, 3–10, 11–19, 20+). Results Descriptive analysis, largely confirmed by logistic regression, demonstrated that greater numbers of prescription opioid fills were associated with greater likelihood of CUD. This relationship was reduced somewhat for those receiving the most opioid prescriptions (20+) in the logistic regression, which controlled for potentially confounding variables. Discussion and Conclusions These results warrant increased attention to CUDs among patients receiving numerous opioid prescriptions. Increasing legalization of cannabis is likely to further increase use and abuse of cannabis in patients prescribed opioids. Scientific Significance These findings suggest that clinicians should be alert to concomitant CUD and prescription opioid use, as these substances appear to complement each other. (Am J Addict 2015;24:538–545)